Developmental delay in 3-month-old low birth weight infants with hyperbilirubinemia - Wiradharma Wiradharma; I Gusti Ayu Trisna Windiani; Ekawaty Lutfia Haksari (Indonesian Pediatric Society, 2013)
Backgrourui Developmental delay may be due to a variety offactors occurring during the prenatal, perinatal, or postnatalperiods, one of which is hyperbilirubinemia.Objective To evaluate the impact ofhyperbilirubinemia on infantdevelopmental delay.Methods A prospective cohort study was conducted from March toJuly 2011. Subjects were low birth weight infants with and withouthyperbilirubinemia. Developmental delay was measured using theMullen Scales of Early Learning. Data was analyzed by Chi squaretest and relative risks were calculated. Logistic regression analysiswas performed to assess factors associated with developmentaldelay. Differences were considered statistically significant for Pvalues < 0.05.Results Forty-six low birth weight infants were enrolledin this study, 23 with hyperbilirubinemia and 23 withouthyperbilirubinemia. The relative risk (RR) for developmentaldelay in the hyperbilirubinemia group was 2.08 (95%CI 0.51 to8 .40). Multivariate analysis revealed that hyperbilirubinemia didnot significantly influence developmental delay (RR 1.45; 95%CI0.29 to 7.31). However, small for gestational age with or withouthyperbilirubinemia significantly influenced developmental delay(RR 12.13; 95%CI 2.43 to 60.56).Conclusion Hyperbilirubinemia in low birth weight infants isn ot a risk factor for developmental delay at the age of 3 months.However, being small for gestational age with or withouthyperbilirubinemia significantly influences the likelihood ofdevelopmental delay.